2015
DOI: 10.1038/bjc.2015.324
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer risk at low radon exposure rates in German uranium miners

Abstract: Background:A determination of the risk of lung cancer at low levels of radon exposure is important for occupational radiation protection.Methods:The risk of death from lung cancer at low radon exposure rates was investigated in the subcohort of 26 766 German uranium miners hired in 1960 or later.Results:A clear association between lung cancer mortality (n=334 deaths) and cumulative exposure to radon in working level months (WLM) was found. The excess relative risk per WLM was 0.013 (95% confidence intervals: 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
75
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 9 publications
7
75
2
2
Order By: Relevance
“…A past update of this cohort with follow-up to 1977 observed an ERR per 100 WLM of 1.50 for lung cancer mortality 23. A recent study by Kreuzer et al 33 also examined the risk of lung cancer mortality from low radon exposure rates among a subcohort of miners hired in 1960 or later and observed an ERR/100 WLM of 1.30 (95% CI 0.70 to 2.10). In reviewing other studies that have examined low-dose radon exposure, Kreuzer et al observed that the ERR/100 WLM estimates from these studies ranged from 0.40 to 4.20, which is consistent with our mortality estimate of 0.66 WLM/100 WLM.…”
Section: Discussionmentioning
confidence: 99%
“…A past update of this cohort with follow-up to 1977 observed an ERR per 100 WLM of 1.50 for lung cancer mortality 23. A recent study by Kreuzer et al 33 also examined the risk of lung cancer mortality from low radon exposure rates among a subcohort of miners hired in 1960 or later and observed an ERR/100 WLM of 1.30 (95% CI 0.70 to 2.10). In reviewing other studies that have examined low-dose radon exposure, Kreuzer et al observed that the ERR/100 WLM estimates from these studies ranged from 0.40 to 4.20, which is consistent with our mortality estimate of 0.66 WLM/100 WLM.…”
Section: Discussionmentioning
confidence: 99%
“…We were further forced to make some assumptions, e.g. no participant of a TRICL/ILCCO study was substantial long-term exposed to radon ( WLM < 50) However, even long-term but low-dose exposure to radon, occupational (Kreuzer et al 2015) as well as residential (Darby et al 2005), was previously associated with a small increase in lung cancer risk. Thus, the small risk of misclassifying few of the many participants of a TRICL/ILCCO study is more likely for cases than for controls.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, research has shown that risk of lung cancer from breathing radon in with air is much larger than risk of stomach cancer from consumption of water containing radon [8][9][10][11]. Therefore, the main risk connected with radon in water comes from radon released into the air when water is used for showering and other household purposes.…”
Section: Introductionmentioning
confidence: 99%